Mentoring Activity of Pong’s Cassava Chips Industry in Ponggang Village - Wibawa Prasetya; Christine Natalia; Marsellinus Bachtiar Wahyu; Riana Magdalena (MITRA: Jurnal Pemberdayaan Masyarakat, 2018)
PONG's cassava chips are snack products that have a unique flavor and aroma compared to other similar products. The specialty of this product is due to its traditional processing and its use of the original spice from the village of Ponggang, Subang, west Java. The snacks are currently sold just around the village of Ponggang and traditional markets. The product packaging looks very simple. The community service team aims to increase the product sales volume by improving the packaging design, listing the P-IRT number obtained by registering to the Subang Regency Health Office, providing simple bookkeeping training, providing product processing training based on UU No. 18 of 2012 on Food, provides training on how to expand the marketing network. The method used is business assistance and the target partner is Ponggang Independent Women group. As a result our community service program, independent women group members can manage their own P-IRT permit, can do simple bookkeeping, can apply Law No. 18 of 2012 on Food in producing PONG's cassava chips. It is suggested that continuous assistance should be provided to the industry so that the vision and mission of independent women groups can be implemented successfully.